The Association of Fruits and Vegetables Consumption and COVID-19: Results from Yazd Health Study and TAMYZ Study - Hassanizadeh, Shirin; Mohammadi, Vida; Nadjarzadeh, Azadeh; Mirzaei, Masoud; Hosseinzadeh, Mahdieh (Current Nutrition & Food Science, 2025)
BackgroundCOVID-19 has caused a high health burden worldwide and increased the need to identify factors affecting its risk. Fruits and vegetables are essential for a healthy diet and immune system function. This study investigated the associations between fruit and vegetable intake and COVID-19 incidence in a large sample of Iranian adults.MethodsIn this cross-sectional study, we used data from 9189 participants of Yazd Health Study (YaHS) and Taghzieh Mardom-e-Yazd (TAMIZ) study aged 20 to 70 years. Dietary intakes were assessed using a validated food frequency questionnaire (FFQ).ResultsAfter adjusting for confounding variables, we found that higher intake of total fruit (OR: 0.42, CI: 0.20–0.83, P-trend =0.05), fresh fruit (OR: 0.46, CI: 0.23– 0.92, P-trend =0.04), green leafy vegetables (OR: 0.48, CI: 0.24–0.96, P-trend =0.08), and vitamin C (OR: 0.38, CI: 0.17– 0.81, P-trend =0.02) were associated with lower odds of COVID-19. No significant associations were observed for fruit juice, dried fruit, fruit compote, cruciferous vegetables, yellow vegetables, total vegetables and dietary fiber intake.ConclusionOur study suggests that higher consumption of fresh fruit, total fruit, green leafy vegetables, and dietary vitamin C may reduce the risk of COVID-19. Further studies are needed to confirm these findings and provide evidence-based nutritional recommendations. Furthermore, the current study's findings could be important for similar pandemics.
Keywords: Yazd Health Study